Fathers’ mental health and coping strategies: a qualitative study in Mwanza, Tanzania - Sylvia Kaaya; Marilyn N Ahun; Joshua Jeong; Juliet K McCann; Damas Joachim; Mary Kabati (BMJ Open, 2024)
Objectives To investigate the nature of paternal mental health problems, their causes and the coping strategies used by fathers of young children under the age of 2 years.Design and setting We conducted in-depth interviews with fathers, mothers, community leaders and community health workers as well as focus group discussions with fathers-only, mothers-only and mixed groups of fathers and mothers. Respondents provided their perspectives on the psychosocial challenges affecting fathers and how fathers responded to their mental health problems. Data were triangulated across stakeholders and analysed using thematic content analysis.Setting The study was conducted in four communities in Mwanza, Tanzania.Participants The total sample included 56 fathers, 56 mothers and 8 community stakeholders that were equally distributed across the four communities.Results Respondents highlighted a spectrum of mental health concerns affecting fathers, including elevated parenting stress, depressive symptoms, and anxiety. Causes of paternal mental health problems included poverty, child-related concerns, marital problems and family illness. When asked about paternal coping strategies, both fathers and mothers shared that fathers mostly turned to negative coping strategies to manage their distress, such as paternal alcohol use and poor conflict resolution strategies. However, respondents also shared how some fathers used positive coping strategies, such as seeking out social support from their family and friends, engaging in exercise and leisure activities and relying on their faith.Conclusions Overall, this study highlights the importance of supporting positive mental health among fathers. Our findings can inform the design of psychosocial programme components that can be integrated within parenting interventions to promote the well-being of specifically fathers and ultimately improve the family caregiving environment.